Pemberdayaan Mahasiswa Melalui Program Renjani (Relawan Pajak Untuk Negeri): Kolaborasi Kanwil Djp Riau dan Tax Center Universitas Islam Negeri Sultan Syarif Kasim Riau - Sahwiti Triandani; Irien Violinda Anggriani (Unri Conference Series: Community Engagement, 2025)
Students as the younger generation and prospective taxpayers are important entities that need to be involved in national development. This community service activity is carried out in relation to the Tax Volunteer Program for the Nation (Renjani), a National Program of the Directorate General of Taxes of the Republic of Indonesia involving a number of universities, both private and state-owned, throughout Indonesia. The community service team, in collaboration with the Riau Regional Office of the Directorate General of Taxes and the Tax Center of UIN Sultan Syarif Kasim Riau, is involved in Renjani activities from socialization, recruitment, selection, implementation until the program ends. Renjani has a significant contribution in providing education, technical assistance, and direct mentoring to taxpayers in the process of reporting Annual Tax Returns, especially within the academic community of UIN Sultan Syarif Kasim Riau. The presence of Renjani not only has a positive impact on increasing the number of Tax Return reports, but also strengthens the role of the Tax Center as a strategic partner of the Directorate General of Taxes (DGT) in building tax awareness and compliance from an early age. In addition, this activity also serves as a forum for developing volunteer competencies in the fields of taxation and public service. Therefore, assistance and support from all parties are needed so that the Renjani program can be successful in supporting national development in the field of taxation and implementing collaboration between universities and institutions throughout Indonesia.